ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMBELIAN KOPI BUBUK PADA RUMAH TANGGA DI KECAMATAN CURUP UTARA KABUPATEN REJANG LEBONG - Tri Wahyuningsih; M. Mustopa Romdhon; Reswita, Reswita (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Ground coffee is a drink that has become a lifestyle nowadays. Ground coffee is made from processed coffee that is roasted and then processed to become coffee powder. Currently, the number of requests for ground coffee products is quite high in the market. The aims of this study were to 1) analyze the level of purchase of ground coffee by households in North Curup District, 2) analyze what factors influence the level of purchase of ground coffee by households in North Curup District. The method used to determine the location of this study is purposive or intentional with the consideration that in Curup Utara District there are several coffee production businesses. Respondents were determined by the Accidental Sampling method and obtained as many as 96 respondents. The data analysis method used is multiple linear regression analysis method. Based on the results of the study, 1) The level of ground coffee purchases by Curup Utara District is in the low category, with an average purchase of 872.4 grams/month, 2) The factor that has a significant effect is the household income variable. While the variables of the number of adult family members, education level, consumer age and perceptions of the product have no significant effect on the purchase level of ground coffee in Curup Utara District